Clinical benefit of controversial first line systemic therapies for advanced stage ovarian cancer – ESMO-MCBS scores. (September 2018) - Broekman, K.E.; Jalving, M.; van Tinteren, H.; Sessa, C.; Reyners, A.K.L.
Highlights: Advanced ovarian cancer first line therapy trials are scored on the ESMO-MCBS. Intraperitoneal cisplatin, dose-dense paclitaxel and bevacizumab are discussed. Of these, only bevacizumab should be considered in first line, in the high-risk population. Abstract: Background: The magnitude of clinical benefit scale (MCBS) was introduced by the European Society of Medical Oncology (ESMO) to quantify the clinical benefit of therapeutic regimens and to prioritise therapies. It distinguishes curative from palliative treatments and ranks their benefit based on overall survival (OS), progression free survival (PFS), quality of life (QoL) and toxicity. Objective of this study on the first line treatment of ovarian cancer was to evaluate the evidence for the current standard of care using the ESMO-MCBSv1.1 with an emphasis on controversial therapeutic options: intraperitoneal chemotherapy, dose-dense paclitaxel and bevacizumab. Methods: Phase III trials, published since 1992, investigating first line systemic treatment of Fédération Internationale de Gynécologie et d'Obstétrique (FIGO) stage IIB-IV epithelial ovarian cancer were included. Since most studies included patients with FIGO stage IV disease or incomplete debulking, all treatments were judged to be palliative. Treatments were graded 5 to 1 on the ESMO-MCBSv1.1, where grades 5 and 4 represent a high level of clinical benefit. Results: 55 studies met the inclusion criteria. ESMO-MCBS scores were calculated for eleven studies that showed a statistically significant benefit of the experimental treatment. Intraperitoneal (ip) cisplatin scored a 4 and 3, but two other studies were negative and therefore not scored on the ESMO-MCBS. Dose-dense paclitaxel showed substantial clinical benefit in one study (score 4), but three studies were negative. Addition of bevacizumab also scored a 4 in one study subgroup including high-risk patients but a 2 in another trial with a larger study population. Conclusion: Based on ESMO-MCBS scores, dose-dense paclitaxel and intraperitoneal chemotherapy cannot be recommended as standard treatment. Bevacizumab should be considered only in the high-risk population. The ESMO-MCBSv1.1. helps to summarise reported studies on controversial treatment regimens, and identifies their weaknesses.